2005
DOI: 10.1542/peds.2005-1035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognostic Factors of Disability After Childhood Injury

Abstract: ABSTRACT. Objective. To assess the prevalence and the prognostic factors of disabilities after minor and major childhood injuries and to analyze which sociodemographic and injury-related factors are predictive for suboptimal functioning in the long term.Method. We conducted a patient follow-up study in a stratified sample of 1221 injured children who were aged 5 to 14 years and had visited an emergency department in the Netherlands. Our study sample was stratified so that severe, less common injuries were over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 30 publications
5
62
0
4
Order By: Relevance
“…This observation corresponds with findings reported by Polinder et al 2 and Gofin et al, 3 who found, respectively, that 48.7% and 65% of injuries sustained by children occur at home. A possible argument in support of this observation could be that many parents are absent from home during the afternoon, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This observation corresponds with findings reported by Polinder et al 2 and Gofin et al, 3 who found, respectively, that 48.7% and 65% of injuries sustained by children occur at home. A possible argument in support of this observation could be that many parents are absent from home during the afternoon, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…It could be recommended that one of the senior doctors in the emergency department should receive further training in orthopaedics to minimise the number of referrals. Polinder et al 2 found that 75% of children with lasting disabilities were treated for their injuries at the emergency department only and not referred for specialist attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our results the YLD for noniadmitted injury patients are underi i estimated owing to incomplete DALY estimates; for some frequently occurring injuries (concussion, superficial injury), no disability weights were estimated in the GBD study. Among these primarily noniadmitted patients, there is a small proportion with longiterm disability, which may lead to a high estimate of prevalence of disability owing to high annual numbers of patients, 16,17 and thus results in an underestimation of YLD. Although burns are a very disabling type of injury, they were excluded from our analysis.…”
mentioning
confidence: 99%
“…In our results the YLD for non-admitted injury patients are underestimated owing to incomplete DALY estimates; for some frequently occurring injuries (concussion, superficial injury), no disability weights were estimated in the GBD study. Among these primarily non-admitted patients, there is a small proportion with long-term disability, which may lead to a high estimate of prevalence of disability owing to high annual numbers of patients, 16,17 and thus results in an underestimation of YLD. Although burns are a very disabling type of injury, they were excluded from our analysis.…”
mentioning
confidence: 99%